2023
DOI: 10.1002/adfm.202304228
|View full text |Cite
|
Sign up to set email alerts
|

Superionic Silver Halide Solid Electrolyte: Dielectric Property and Iontronic Memtransistor Application for Bioinspired Computing

Arka Mukherjee,
Kannan Udaya Mohanan,
Srikrishna Sagar
et al.

Abstract: Technology like high‐level parallel information processing and storage in the brain remains a dream to the researchers using conventional solid‐state electronics. Here, a robust thin film bilayer superionic dielectric of poly(ethylene oxide) (PEO) and rubidium silver iodide (RbAg4I5) is developed to fabricate solid‐state iontronic synaptic memtransistors, which can serve as the basic building blocks for the hardware‐implementation of neuromorphic computing. X‐ray photoelectron spectroscopy and impedance measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…For the Off-state, both Z and φ show a plateau and a dip, respectively, at the low-frequency side in Figure a, which indicate slow carrier diffusion and accumulation similar to electrical double-layer formation (EDL) near the electrode and MoS 2 interfaces. This is nicely supported by the modeled RC-equivalent circuit (inset of Figure b) containing a 335 pF constant phase element (CPE) for the nonideal EDL capacitor with α value 0.996 and a 56.3 MΩ/√s Warburg impedance ( W ) for carrier diffusion near the electrodes with the regular components of contact resistance (33.8 Ω), bulk resistance (98.0 MΩ), and metal–insulator–metal (MIS) device capacitance (1.71 nF) . These features are also reflected in the Nyquist plot for the Off-state before the SET process, as shown in Figure b, which offers a semicircle at the high-frequency side near the origin due to the interfacial carrier kinetics followed by a linear portion having an angle about 45° with the abscissa representing the diffusion of carriers at the low-frequency side.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…For the Off-state, both Z and φ show a plateau and a dip, respectively, at the low-frequency side in Figure a, which indicate slow carrier diffusion and accumulation similar to electrical double-layer formation (EDL) near the electrode and MoS 2 interfaces. This is nicely supported by the modeled RC-equivalent circuit (inset of Figure b) containing a 335 pF constant phase element (CPE) for the nonideal EDL capacitor with α value 0.996 and a 56.3 MΩ/√s Warburg impedance ( W ) for carrier diffusion near the electrodes with the regular components of contact resistance (33.8 Ω), bulk resistance (98.0 MΩ), and metal–insulator–metal (MIS) device capacitance (1.71 nF) . These features are also reflected in the Nyquist plot for the Off-state before the SET process, as shown in Figure b, which offers a semicircle at the high-frequency side near the origin due to the interfacial carrier kinetics followed by a linear portion having an angle about 45° with the abscissa representing the diffusion of carriers at the low-frequency side.…”
Section: Resultsmentioning
confidence: 58%
“…This is nicely supported by the modeled RC-equivalent circuit (inset of Figure 4b) containing a 335 pF constant phase element (CPE) for the nonideal EDL capacitor with α value 0.996 and a 56.3 MΩ/√s Warburg impedance (W) for carrier diffusion near the electrodes with the regular components of contact resistance (33.8 Ω), bulk resistance (98.0 MΩ), and metal−insulator−metal (MIS) device capacitance (1.71 nF). 39 These features are also reflected in the Nyquist plot for the Off-state before the SET process, as shown in Figure 4b, which offers a semicircle at the highfrequency side near the origin due to the interfacial carrier kinetics followed by a linear portion having an angle about 45°w ith the abscissa representing the diffusion of carriers at the low-frequency side. Most interestingly, a capacitance of 280 pF is estimated from the series combination of C and CPE, which is almost equal to the measured capacitance value (Figure S11 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 79%
“…By utilizing XPS measurements and density functional theory (DFT) analysis, they could assess the role of mobility and carrier density in modulating the conductance of protonated WO 3 . A gate-controlled iontronic memtransistor device based on a bilayer thin film of poly(ethylene)oxide(PEO), and rubidium silver iodide (RbAg 4 I 5 ) was recently reported by A. Mukherjee et al [ 80 ], where the Ag + ionic movement inside the RbAg 4 I 5 layer was found responsible for the resistive switching mechanism. Interestingly, the device exhibited rich physics, like colossal hysteresis and negative differential transconductance, revealing interesting research possibilities in these devices.…”
Section: Resistive Switchingmentioning
confidence: 99%
“…The correlation between accuracy in different neural morphology devices and epochs is also summarized in Figure 4e; and Table S4 (Supporting Information). [20,40,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] In the future, developing a neural morphology chip that integrates the functions of perception, storage, and computation is necessary. Previously, photodiode-configured optoelectronic synapses demonstrated excellent storage properties and potential in neuromorphic computation.…”
Section: Neuromorphic Computation Based On Perovskite Photoelectric S...mentioning
confidence: 99%